An inquiry into ethnicity in the structures of the church: the case of Malawi - Zgambo, Humphreys Frackson (Open Science Journal, 2017)
Ethnicity, tribalism and xenophobia could be found inside and outside church walls. Ethnic and racist behaviours in human beings are natural, learned and nurtured within societies around the world. However, ethnic identity and relations exist whether the ethnic groups are competing or not. The first challenge of the early church in the New Testament Church was to overcome ethnicity and hostile divisions between Jews and Gentles. The New Testament Church’s principles of open plural government overcame the phenomenon. The contemporary church is in dilemma to understand its archaic church polity and order in her own challenging context today.